2006
DOI: 10.1152/ajpendo.00058.2006
|View full text |Cite
|
Sign up to set email alerts
|

Continuous testosterone administration prevents skeletal muscle atrophy and enhances resistance to fatigue in orchidectomized male mice

Abstract: . Continuous testosterone administration prevents skeletal muscle atrophy and enhances resistance to fatigue in orchidectomized male mice. Am J Physiol Endocrinol Metab 291: E506 -E516, 2006. First published April 18, 2006 doi:10.1152/ajpendo.00058.2006.-Androgens promote anabolism in skeletal muscle; however, effects on subsequent muscle function are less well defined because of a lack of reliable experimental models. We established a rigorous model of androgen withdrawal and administration in male mice and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
90
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(105 citation statements)
references
References 72 publications
11
90
3
Order By: Relevance
“…All mouse lines were back-crossed to a congenic C57BL/6 background (>10 generations back-cross), and control littermates (AR lox hemizygous males, cre heterozygous males and wildtype (WT) males) were used for both lines. We also analyzed gene expression in gastrocnemius muscle from our previously described global AR ΔZF2 and androgen deprivation models: WT and global AR ΔZF2 , 9 weeks of age, n ≥ 24, and WT C57BL/6 orchidectomized males treated ± testosterone for 10 weeks, 8 weeks of age, n ≥ 8 (Axell et al 2006, MacLean et al 2008b). Mice were housed in a conventional facility, and standard chow and water provided ad libitum.…”
Section: Micementioning
confidence: 99%
See 1 more Smart Citation
“…All mouse lines were back-crossed to a congenic C57BL/6 background (>10 generations back-cross), and control littermates (AR lox hemizygous males, cre heterozygous males and wildtype (WT) males) were used for both lines. We also analyzed gene expression in gastrocnemius muscle from our previously described global AR ΔZF2 and androgen deprivation models: WT and global AR ΔZF2 , 9 weeks of age, n ≥ 24, and WT C57BL/6 orchidectomized males treated ± testosterone for 10 weeks, 8 weeks of age, n ≥ 8 (Axell et al 2006, MacLean et al 2008b). Mice were housed in a conventional facility, and standard chow and water provided ad libitum.…”
Section: Micementioning
confidence: 99%
“…Androgens are also required to increase muscle mass in adult males. Androgen withdrawal-dependent muscle atrophy has been demonstrated in both normal men and men with prostate cancer undergoing androgen ablation therapy (Mauras et al 1998, Basaria et al 2002, with a similar decrease in muscle mass occurring following orchidectomy in male mice (Axell et al 2006). Because testosterone levels decline in aging males, this may be one mechanism contributing to age-related sarcopenia.…”
Section: Introductionmentioning
confidence: 99%
“…Increase in muscle mass depends on protein synthesis, being it influenced by the endogenous responses of the many anabolic hormones, among which, we highlight testosterone 3 . This hormone is necessary for maintenance of muscular mass and anabolism in humans, although it occurs by ways somehow not very clear yet, but it is important for the structure and function of the skeletal muscle 4 . Kuoringet al 5 observed increase of isometric strength and muscular mass of lower limbs, corroborating the interaction between endogenous testosteroneand androgenic receptors (AR) in the recovery phase, with consequent increase of protein synthesis, muscular hypertrophy and strength.…”
Section: Introductionmentioning
confidence: 99%
“…Since aging is regularly associated with a gradual decline in circulating testosterone concentrations and decreased musculature in men, AAS replacement therapies have been currently suggested to circumvent the age--related morbidity and cognitive impairment in men (Dillon et al2010). Accordingly, supra--physiologic (50 nM = 50--fold normal) dosing of testosterone for eight continuous weeks has been shown protective to muscle mass and fatigue resistance in orchiectomized mice compared to sham operated animals (Axell et al 2006). The protective action of testosterone on skeletal muscle and cognitive capacities may in part be due to its anti--inflammatory actions or through direct modulation of anti--catabolic pathways (Thompson et al 2006;Liva and Voskuhl 2001;Malkin et al 2004).…”
mentioning
confidence: 99%